2016
DOI: 10.4067/s0717-95022016000400007
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Study of Aquaporin 1 and 2 in the Reproductive Tract of the Bactrian camel (Camelus bactrianus)

Abstract: SUMMARY:Spermatogenesis is associated with considerable fluid secretion or absorption in the male reproductive tract. Aquaporins (AQPs) are membrane protein channels that allow the rapid movement of water through epithelium. In the present study, immunohistochemistry was utilized to localize the expression of AQP 1, AQP2 in the testis and prostate of adult bactrian camel (Camelus bactrianus). Results show that AQP1 have intense reaction in rete testis, efferent ducts, vessels, seminiferous duct and in the pros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Prostatic secretion of prostate fluid is one of the important components of semen; it provide nutrients and a suitable environment for sperm. An and Wang [ 27 ] reported that AQP1 and AQP2 were localized in the prostate, showing that the water channel protein is closely related to the function and may influenced the transportation of sperm and nutrition. Our present finding showed that the immune reactivity of anti-AQP-7 antibody was intense in both compact and disseminated parts of the prostate gland during the rutting season.…”
Section: Discussionmentioning
confidence: 99%
“…Prostatic secretion of prostate fluid is one of the important components of semen; it provide nutrients and a suitable environment for sperm. An and Wang [ 27 ] reported that AQP1 and AQP2 were localized in the prostate, showing that the water channel protein is closely related to the function and may influenced the transportation of sperm and nutrition. Our present finding showed that the immune reactivity of anti-AQP-7 antibody was intense in both compact and disseminated parts of the prostate gland during the rutting season.…”
Section: Discussionmentioning
confidence: 99%
“…Many reports have demonstrated the expression of AQP proteins in the male reproductive system in different mammalian species such as humans ( Pastor-Soler et al, 2001 ), rodents ( Calamita et al, 2001a , 2001b ; Lu et al, 2008 ; Ford et al, 2014 ), Bactrian camel ( An & Wang 2016 ), stallion ( Klein et al, 2013 ), bat ( Oliveira et al, 2013 ), cat ( Arrighi & Aralla 2014 ), and dog ( Domeniconi et al, 2007 ). The expression and localization of AQP proteins in the male reproductive tissues are variable among the tested mammalian species ( Boj et al, 2015 ; Carrageta et al, 2020 ; Ribeiro et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%